PROSE NARRATION AND CONTENT HARMONY IN ALISHER NAVOI’S WORKS - Ozoda Tojiboyeva (Galaxy International Interdisciplinary Research Journal, 2024)
The following article is dedicated to Alisher Navoi’s work "Khamsa", and artists over the centuries by various cases of clear prose. It is also drawn attention to adjust the interpretation of the works of changes in attitude to the works of art, the analysis of the level of understanding of the classical works of the reader.